2016
DOI: 10.1111/1753-0407.12478
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of tumor necrosis factor‐α, monocyte chemoattractant protein‐1, and adiponectin genes in visceral adipose tissue is related to type 2 diabetes in the Xinjiang Uygur population

Abstract: Lower ADIPOQ and higher TNF and MCP1 mRNA expression in visceral adipose tissue may be correlated with obesity and T2DM in the Uygur population. Promoter DNA methylation affects expression of ADIPOQ and TNF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
1
12
1
Order By: Relevance
“…Aerobic exercise did not alter the DNA methylation or mRNA expression of either IL6 or TNF. The epigenetic impact of exercise on inflammatory cytokines is relatively unknown, however, several studies have indicated a role for cytokine DNA methylation in inflammatory disease [34][35][36][37]. Although no association between TNF DNA methylation and mRNA expression was detected in the present study, n-3 PUFAs have previously been demonstrated to reverse the epigenetic changes observed with inflammation in skeletal muscle cells.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Aerobic exercise did not alter the DNA methylation or mRNA expression of either IL6 or TNF. The epigenetic impact of exercise on inflammatory cytokines is relatively unknown, however, several studies have indicated a role for cytokine DNA methylation in inflammatory disease [34][35][36][37]. Although no association between TNF DNA methylation and mRNA expression was detected in the present study, n-3 PUFAs have previously been demonstrated to reverse the epigenetic changes observed with inflammation in skeletal muscle cells.…”
Section: Discussioncontrasting
confidence: 81%
“…Increases in markers of oxidative stress and circulating levels of inflammatory cytokines, such as IL-6 and TNFa, have been shown to alter the expression of DNA methyltransferases (DNMTs) [28][29][30][31][32] and influence DNA methylation patterns [11,33]. DNA methylation of inflammatory cytokines have been associated with various inflammatory diseases including IL6 with Rheumatoid Arthritis [34] and obesity [35]; TNF DNA methylation with type 2 diabetes [36] and Alzheimer's disease [37]. Despite increased circulating levels of inflammatory cytokines post-exercise [14,23], the impact of exercise on the DNA methylation of genes encoding inflammatory cytokines such as IL6 and TNF remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Among several factors, a very recent population based study carried out in the USA confirmed that obesity, diabetes mellitus, family history of other malignancy, and smoking independently increase the odds ratio for the occurrence of colorectal cancer [83]. Inflammatory cytokines appear to play a key role in linking obesity and colorectal carcinogenesis particularly so for IL-6 and tumor necrosis factor-α [84,85]; a recent study also describing IL-13 as a potential factor involved in the development of obesity-related colon cancer onset [86]. As it was the case for colon rectal cancer, also for the gastro-esophageal cancer a positive relationship between abdominal obesity and cancer occurrence has been described.…”
Section: Gi Cancermentioning
confidence: 99%
“…Previous studies addressing obesity-related colorectal tumorigenesis focused on the function of several cytokines, including IL-6 and tumor necrosis factor-α. 15,16 However, these previous studies provided information on the role of individual cytokines of interest, and identification of the dominant cytokines involved in CRC tumorigenesis and their dynamic effects on carcinogenesis under obese conditions remain to be elucidated. A high-throughput screening analysis of related cytokines and subsequent mechanistic analysis are needed to address this problem.…”
Section: Introductionmentioning
confidence: 99%